2009
DOI: 10.1371/journal.pone.0004322
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Correlates of Angiographic Coronary Artery Disease

Abstract: Coronary angiography allows a direct evaluation of coronary anatomy. The aim of the present investigation was to search for correlations between the magnitude of coronary artery disease, as assessed by angiography, and a number of systemic parameters. A group of 116 patients (80 male, 36 female) with coronary heart disease diagnosed by angiography, aged 62.0±10.5 years, was the subject of an observational study. Correlation and linear regression analysis using coronary artery disease burden (CADB - sum of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This discrepancy may be due to the limited size of the study population and is mono-centered. However, some studies have shown a strong association of high LDL and low HDL in severity of lesion though, 12,14 normoglycemic individuals had no differences between with CAD and without CAD. 18 Smoking is considered to be one of the major risk factors in CAD 22,23 and the present study has also revealed the significant relation of smoking with coronary stenosis (OR 4.10; CI 1.45 -11.61, p <0.01), which is also supported from previous studies.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…This discrepancy may be due to the limited size of the study population and is mono-centered. However, some studies have shown a strong association of high LDL and low HDL in severity of lesion though, 12,14 normoglycemic individuals had no differences between with CAD and without CAD. 18 Smoking is considered to be one of the major risk factors in CAD 22,23 and the present study has also revealed the significant relation of smoking with coronary stenosis (OR 4.10; CI 1.45 -11.61, p <0.01), which is also supported from previous studies.…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, the greater number of coronary artery diseases is associated with the advancing age (80% ) and male (60%, OR 2.47; CI 0.94 -6.48, p <0.05) population is found to have higher association. On other hand, as diabetes mellitus, hypertension, dyslipidemia and smoking are considered to be the cardiovascular risk factors, [10][11][12][13] the current study has analyzed those cardiovascular risk factorsto see the association with significant coronary artery stenosis. Our study shows the significant association (OR 3.32, CI 1.12 -9.84, p <0.05) between diabetes mellitus and coronary artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The research protocol (including the informed consent forms) was evaluated and approved by an independent ethics committee (Comissão de Ética do Centro de Saúde São João, Porto, Portugal), as previously reported [11]. All participants provided a written informed consent, a consent procedure approved by the ethics committee.…”
Section: Methodsmentioning
confidence: 99%